Control and Safety Analysis of Intensified Chemical Processes - Patle, Dipesh Shikchand; Rangaiah, Gade Pandu (John Wiley & Sons, 2024)
This book covers the basic principles of and recent developments in control and safety analysis of intensified chemical processes, ranging from dynamic simulations and safety analysis to the design and control of important processes. The text discusses general methods and tools such as dynamic simulation and safety analysis as well as design and analysis of important applications in order to provide scientists and engineers with an understanding of the design and safety considerations involved in intensified chemical processes.Sample topics covered in this book include:Simulation and optimization methods, common programs and simulators for simulation and optimization, and interfacing of simulators and optimizersPrograms/simulators for dynamic simulation and control, tuning of controllers, and popular criteria for control assessmentControl of a distillation column with dual steam and hot-oil reboilers, and an energy intensified side-stream extractive distillation for binary azeotropic separationDynamics and control of middle vessel batch distillation with vapor recompression and development of a control structure of intensified biobutanol productionA comprehensive resource on the subject, this book is a highly valuable reference for researchers, students and practitioners interested in process intensification and their applications. The text can be adopted by instructors for use in advanced courses on process control and safety.